Frontispiece: Indolizine–Squaraines: NIR Fluorescent Materials with Molecularly Engineered Stokes Shifts. Issue 51 (12th September 2017) - McNamara, Louis E.; Rill, Tana A.; Huckaba, Aron J.; Ganeshraj, Vigneshraja; Gayton, Jacqueline; Nelson, Rachael A.; Sharpe, Emily Anne; Dass, Amala; Hammer, Nathan I.; Delcamp, Jared H.
Abstract : Indolizine squaraine dyes with impressive Stokes shifts and near infrared absorption spectra are introduced. Their significantly enhanced water solubility is unique for squaraine dyes and makes them good candidates for medical imaging applications. Exceptional fluorescence quantum yields of up to 12% are also observed with emission curves extending beyond 850 nm. For more details, see the Full paper by J. H. Delcamp et al. onpage 12494 ff.